The Lived Experiences of Women Leaders at the University of Dar es Salaam and the State University of Zanzibar (Tanzania Journal for Population studies and Development, 2022)
This paper explores the lived leadership experiences of women leaders at the University of Dar es Salaam (UDSM) and the State University of Zanzibar (SUZA). The study employed the phenomenology research design, and involved a total of 31 participants. Data were generated through semi-structured interviews and documentary review. The study findings revealed that, to become a leader, there are obstacles such as loopholes in university policies, guidelines and leadership, university charters, as well as stated leadership attributes. It was also revealed that leadership capacity-building, self-efficacy and self-esteem and accountability were the strategies used by women to remain in university leadership positions. This paper concludes that women leaders pass through a labyrinth to become and remain leaders. The study recommends that university managements should facilitate the provision of leadership capacity-building, supported by favourable policy environments to enhance the nurturing of women leaders.